INTEGRASI PENDIDIKAN KARAKTER PADA PEMBELAJARAN BERBASIS GAME UNTUK MENGAJARKAN PERILAKU SANTUN DI MEDIA SOSIAL - Sukirman Sukirman (Jurnal Pendidikan Ilmu Sosial, 2017)
The facts show that internet users in Indonesia are dominated by groups of children and adolescents. Internet users have a tendency to access higher social media than to dig out entertainment content, news, education, commercial, and public service. Internet-based social media is the easiest and fastest distribution of information, so the chances of bad behavior become quite high. This study aims to teach politeness behavior in social media interactions, especially for adolescents. The research method used is the research literature, namely the assessment and critical and in-depth evaluation of existing research to create new formulas or propose new method related to the problems. Based on the literature review and its discussion,  it can be concluded that character education can be instilled in adolescents to behave courteously in using social media through video game games. Parental guidance needs to be done to avoid bad activities in the use of social media and video games at once.